Selection of potential probiotic candidate bacteria from seawater and shrimp pond sediments for controlling the pathogenic Vibrio parahaemolyticus - Zulfani, Anisa; Yuhana, Munti; Sukenda, Sukenda; Afif, Usamah (Jurnal Akuakultur Indonesia, 2025)
Vibrio parahaemolyticus is one of the pathogenic bacteria that cause vibriosis. V. parahaemolyticus strain that expresses the PirA and PirB toxins is the main causative agent of Acute Hepatopancreatic Necrosis Disease which causes necrosis (cell death) suddenly in the hepatopancreatic organs of shrimp. The environmentally friendly approach to prevent bacterial infections in shrimp is through the application of probiotics. Probiotic isolates originated from the same environment as the host and pathogen were expected to have a better adaptation and competition capability. Probiotic selection begins with the process of searching for and screening the potential probiotic candidates. This study aims to obtain isolates and characterize the potential probiotic bacteria isolated from seawater and pond sediments as an inhibition effort V. parahaemolyticus. The research was conducted experimentally using a completely randomized design with 3 treatments and 2 replicates in the in vitro antagonistic test as well as the in vivo non-pathogenicity test. The results of the study successfully obtained 37 probiotic candidate isolates with 10 isolates having the greatest enzyme activity. LAZ-2 (Acinetobacter radioresistens) isolated from seawater and SAZ-22 (Fusobacterium varium) isolated from pond sediment have been selected as probiotic candidate bacteria that have beneficial enzymatic activities. Both isolates were capable of inhibiting the growth of the pathogenic V. parahaemolyticus cells population and both were not pathogenic to vannamei shrimp. Keywords: probiotic, screening, vannamei shrimp, Vibrio parahaemolyticus ABSTRAK Vibrio parahaemolyticus merupakan salah satu bakteri patogen penyebab penyakit vibriosis. V. parahaemolyticus strain tertentu yang mengekspresikan toksin PirA dan PirB merupakan agen penyebab utama Acute Hepatopancreatic Necrosis Disease yang menyebabkan nekrosis (kematian sel) secara tiba-tiba pada organ hepatopankreas udang. Pendekatan yang ramah lingkungan untuk mencegah penyakit infeksi bakterial pada udang adalah melalui aplikasi probiotik. Isolat-isolat probiotik yang berasal dari lingkungan yang sama dengan inang dan patogen akan memiliki suatu kemampuan adaptasi dan kompetisi yang lebih baik dari yang lainnya. Seleksi probiotik diawali dengan proses pencarian dan skrining kandidat probiotik yang potensial. Penelitian ini bertujuan untuk mendapatkan isolat dan mengkarakterisasi bakteri probiotik potensial yang diisolasi dari air laut dan sedimen tambak sebagai upaya penghambatan V. parahaemolyticus. Penelitian dilakukan secara eksperimental menggunakan Rancangan Acak Lengkap (RAL) dengan 3 perlakuan dan 2 kali ulangan pada uji antagonistik in vitro dan uji non-patogenisitas. Hasil penelitian berhasil mendapatkan 37 isolat kandidat probiotik dengan 10 isolat yang memiliki aktivitas enzim terbesar. LAZ-2 (Acinetobacter radioresistens) yang diisolasi dari air laut dan SAZ-22 (Fusobacterium varium) yang diisolasi dari sedimen tambak terpilih sebagai bakteri kandidat probiotik yang memiliki aktivitas enzim yang menguntungkan. Kedua isolat tersebut mampu menghambat pertumbuhan populasi sel patogen V. parahaemolyticus dan keduanya tidak bersifat patogenik terhadap udang vaname. Kata kunci: probiotik, seleksi, udang vaname, Vibrio parahaemolyticus